The 8q24 region hosts miRNAs altered in biospecimens of colorectal and bladder cancer patients. (10th November 2022) - Gagliardi, Amedeo; Francescato, Giulia; Ferrero, Giulio; Birolo, Giovanni; Tarallo, Sonia; Francavilla, Antonio; Piaggeschi, Giulia; Di Battista, Carla; Gallo, Gaetano; Realis Luc, Alberto; Sacerdote, Carlotta; Matullo, Giuseppe; et al.
Abstract: Background: The 8q24 locus is enriched in cancer‐associated polymorphisms and, despite containing relatively few protein‐coding genes, it hosts the MYC oncogene and other genetic elements connected to tumorigenesis, including microRNAs (miRNAs). Research on miRNAs may provide insights into the transcriptomic regulation of this multiple cancer‐associated region. Material and methods: We profiled all miRNAs located in the 8q24 region in 120 colorectal cancer (CRC) patients and 80 controls. miRNA profiling was performed on cancer/non‐malignant adjacent mucosa, stool, and plasma extracellular vesicles (EVs), and the results validated with The Cancer Genome Atlas (TCGA) data. To verify if the 8q24‐annotated miRNAs altered in CRC were dysregulated in other cancers and biofluids, we evaluated their levels in bladder cancer (BC) cases from the TCGA dataset and in urine and plasma EVs from a set of BC cases and healthy controls. Results: Among the detected mature miRNAs in the region, 12 were altered between CRC and adjacent mucosa (adj. p  < 0.05). Five and four miRNAs were confirmed as dysregulated in the CRC and BC TCGA dataset, respectively. A co‐expression analysis of tumor/adjacent tissue data from the CRC group revealed a correlation between the dysregulated miRNAs and CRC‐related genes ( PVT1 and MYC ) annotated in 8q24 region. miR‐30d‐5p and miR‐151a‐3p, altered in CRC tissue, were also dysregulated in stool of CRC patients and urine of BC cases, respectively. Functional enrichment of dysregulated miRNA target genes highlighted terms related to TP53‐mediated cell cycle control. Conclusions: Altered expression of 8q24‐annotated miRNAs may be relevant for the initiation and/or progression of cancer. Abstract : The work provided new insights into the transcriptomic regulation of the 8q24 locus, a region enriched in multiple cancer‐associated polymorphisms. Among the 54 mature miRNAs in the region, 12 were altered in colorectal cancer tissues with 5 miRNAs validated in TCGA dataset. miR‐30d‐5p and miR‐151a‐3p resulted also dysregulated in stool of CRC patients and urine of bladder cancer cases, highlighting the importance of 8q24‐annotated miRNAs for the initiation and/or progression of cancer.